Ramucirumab for advanced gastric cancer or gastro-oesophageal junction adenocarcinoma - Kate Young; Elizabeth Smyth; Ian Chau (Therapeutic Advances in Gastroenterology, 2015)
Ramucirumab, a fully humanized monoclonal antibody directed against vascular endothelial growth factor receptor 2, is the first targeted agent to have demonstrated an improvement in survival, as a single agent or in combination, in a molecularly unselected population in gastro-oesophageal cancer. Now that second-line treatment is routinely considered for patients with advanced gastro-oesophageal cancer, ramucirumab, with its favourable toxicity profile compared with cytotoxic treatment, provides a valuable additional treatment option.